Transactional Lean: Preparing for the Digitalization Era A Systematic Approach to Industrialize Office Processes - Rüttimann, Bruno G. (Springer International Publishing : Imprint: Springer, 2019)
More than 70% of people are working in offices or service industries still applying inefficient processes bearing Muda. However, they are not yet conscious that digitalization will change their life. Whereas during the last years many manufacturing shopfloors have been optimized according to Lean principles preparing for Industry 4.0, Lean management initiatives in the offices often failed or have not exploited the full potential of Lean. The causes might be attributable to the fact that Lean Office initiatives seldom went beyond 5S, VSM, and searching for the seven wastes - they lacked the holistic integrated approach; indeed, how to apply TPM, SMED, or flow on pull in office processes? This book goes beyond searching for Muda by Gemba walk; the aim is to industrialize the office environment in view of the new digitalization challenge by applying the same principles of Lean industry. Whereas the basic process theory remains valid, the Lean tools have to be adapted and transposed to the office characteristics where not machines but employees are at the center of the transactions. Here, a new, already successfully applied, integrated, industry-derived, and systematic approach is presented. It will not only boost office effectiveness and productivity as well as shortening lead-time of office routines far beyond simple Muda elimination, but it will also prepare the processes in view of the upcoming digitalization era.